Opportunities and Challenges in Establishing a Cohort Study: An Example from Cleft Lip/Palate Research in the United Kingdom. (May 2016) - Stock, Nicola Marie; Humphries, Kerry; Pourcain, Beate St; Bailey, Maggie; Persson, Martin; Ho, Karen M.; Ring, Susan; Marsh, Cathy; Albery, Liz; Rumsey, Nichola; Sandy, Jonathan
Background: Cleft lip and/or palate (CL/P) is one of the most common birth conditions in the world, but little is known about its causes. Professional opinion remains divided as to which treatments may be the most beneficial for patients with CL/P, and the factors that contribute to psychological adjustment are poorly understood. The use of different methodological approaches and tools plays a key role in hampering efforts to address discrepancies within the evidence base. A new UK-wide program of research, The Cleft Collective, was established to combat many of these methodological challenges and to address some of the key research questions important to all CL/P stakeholders. Objective: To describe the establishment of CL/P cohort studies in the United Kingdom and to consider the many opportunities this resource will generate. Results: To date, protocols have been developed and implemented within most UK cleft teams. Biological samples, environmental information, and data pertaining to parental psychological well-being and child development are being collected successfully. Recruitment is currently on track to meet the ambitious target of approximately 9800 individuals from just more than 3000 families. Conclusions: The Cleft Collective cohort studies represent a significant step forward for research in the field of CL/P. The data collected will form a comprehensive resource of information about individuals with CL/P and their families. This resource will provide the basis for many future projects and collaborations, both in the United Kingdom and around the world.